If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying W + -19 = 6 + 9w Reorder the terms: -19 + W = 6 + 9w Solving -19 + W = 6 + 9w Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + W = 6 + 19 + 9w Combine like terms: -19 + 19 = 0 0 + W = 6 + 19 + 9w W = 6 + 19 + 9w Combine like terms: 6 + 19 = 25 W = 25 + 9w Simplifying W = 25 + 9w
| 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 | | 3(x+6)=2(3x+15) | | -7x+26.9=-x+29 | | 1in=6ft | | 10(b-8)-4+3b= | | 3c-1=20 | | 6+3x=-12-4x | | 3X+4=5Y+1 | | 3(x+2)-12=5(x+1) | | 11-4x=6-5x+4 | | 9xy-13=40 | | 3y+84=7x | | 6(-3b-3)+6=-120 |